Współpraca województwa lubuskiego z niemieckimi krajami związkowymi - Brandenburgią i Saksonią = The cooperation between the Lubuskie Province and federal states of Germany: Brandenburg and Saxony - Glinka, Kamil (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Due to the solutions of a legal nature, the reform of local self-administration reform of 1998 provided a framework for the activity of provinces on the international arena, including the cooperation with foreign partners. The Lubuskie Province also made use of this opportunity. Therefore, it appears to be justified to present the foundations, aims and forms of the cooperation of the Lubuskie Province with two federal states of Germany: Brandenburg and Saxony, especially, while taking into account the two following elements.
Keywords: pogranicze polsko-niemieckie; stosunki polsko-niemieckie; współpraca polsko-niemiecka; współpraca regionalna; województwo lubelskie; Brandenburgia; Saksonia